DEVELOPING UNDER-RING SHOOTING SKILLS IN TEENAGE BASKETBALL PLAYERS: A PERSPECTIVE ON SPORTS EDUCATION AND LEARNING - Putra, Riken Hadi; Welis, Wilda; Putra, Aldo Naza; Pranoto, Nuridin Widya; Komaini, Anton; Andika, Heru; Ockta, Yovhandra (JETL (Journal of Education, Teaching and Learning), 2024)
This study aims to analyze the role of training motivation in improving the under-the-ring shooting ability of adolescent basketball players. The research method used is a quantitative approach with a descriptive correlational design, involving 15 players aged between 15 to 18 years. Data were collected using a training motivation test with a Likert scale instrument, and the under-the-ring shooting skills were assessed to obtain data on shooting ability. The results of the study indicate that motivation has an influence on under-the-ring shooting, as seen in the significant relationship (0.009 < 0.05), meaning there is a positive correlation between training motivation and under-the-ring shooting ability with a moderate correlation. Therefore, it can be concluded that high training motivation leads to improved shooting performance. To enhance motivation, various forms of support, such as social support and personal achievement, should be provided, as they can contribute positively to players' on-court performance. Future research may consider additional variables such as technique, sports psychology, environmental conditions, and varied training facilities to gain a more comprehensive understanding.